Daycare dilemmas in covid-19 pandemic, should it be opened or not? a case study of a daycare in Yogyakarta - Asma, Syifa Nurul; Susyanto, Bambang Edi; Rusadi, Cici Permata; Wahab, Abdul (BKM Public Health and Community Medicine, 2021)
Objective: Covid 19 pandemic cause changes in various aspects. To avoid the spread of the virus, physical distancing is enforced. Since March 2020 offices and schools have been closed, including the daycare in Yogyakarta. By June 2020 offices have started to enter and some parents will have to work. It becomes a dilemma for stakeholders when parents with children must back to the office to work while the government still restricts daycare opening. This study intends to illustrate the considerations of a daycare in Yogyakarta that was reopened despite being in the red zone of the pandemic and provide alternatives solutions based on a literature review. Method: A qualitative method with a descriptive observational case study approach was used in this study. The data was collected with an interview with one of the daycare owner, and a literature study. Results: The financial needs of managers and daycare employees and the request of the working parents to reopen the daycare became the argument that prompted the reopening of daycare. In general, during this pandemic, the parent's mental health, especially mothers when undergoing dual roles, as mothers and also workers, worsening child’s behaviors and the possibility of violence to children at home are consideration of the need for solutions to this dilemma. Conclusions: Keeping children from the risk of coronavirus transmission should be the priority. The possible alternative solution is the enactment of a home visit by employees of daycare under the supervision of child caregivers, children gathered with a limited number of only one region with attention to health protocols, as well as an invitation for the office to provide a flexible working arrangement for mothers with children.